The Relation between a Naturally Occuring Inhibitor and Prothrombin in Intermediate Product I Formation - Yin, E. T; Shanberge, J. N; Duckert, F (Thrombosis and Haemostasis, 1961)
1. A method for the separation from clotting factors and the concentration of an inhibitor of intermediate product I present in adsorbed plasma and adsorbed serum is described.2. This inhibitor is not only stable but also activated at 37° C. At 4° C it loses activity.3. The inhibitory effect on the formation of intermediate product I is counteracted by small amounts of prothrombin or thrombin.4. After addition of inhibitor prothrombin is necessary for the formation of intermediate product I in the purified system.5. The discrepancy, in regard to the need for prothrombin (or thrombin) between the purified and the non-purified system can be explained by the relative amounts of inhibitor in the two systems.